Participatory research towards the control of snakebite envenoming and other illnesses in a riverine community of the Western Brazilian Amazon. - Alícia Patrine Cacau Santos; Evellyn Antonieta Rondon Tomé Silva; Hiran Sátiro Souza da Gama; Jady Shayenne Mota Cordeiro; Ana Paula Silva Oliveira; Jéssica Albuquerque Araújo; Rafaela Nunes Dávila; Hélio Afonso Amazonas Júnior; Altair Seabra Farias; Jacqueline Almeida Gonçalves Sachett; Vinícius Azevedo Machado; Wuelton Marcelo Monteiro; et al. (PLoS Neglected Tropical Diseases)
Background Riverine communities face various health problems, which involve geographical and cultural barriers to accessing care, in addition to a lack of financial investments in services aimed at these communities, resulting in a process of invisibility for the population living in these regions. In this scenario, the significant burden of snakebite envenoming (SBE) highlights the need for participatory research to address ways to minimize this situation. Thus, this study aimed to describe the priority health problems identified by this population and the ranking of SBEs in that context, mapping solutions according to the local reality. Methodology/principal findings This study was conducted in Limeira, a riverine community located in Tabatinga, in the extreme Western Brazilian Amazonia, on the borders with Peru and Colombia. The research lasted approximately one year, from 2021 to 2022.It is a participatory study that followed three steps: baseline assessment of the community, community assembly, and final data analysis. The study included a total of 42 participants in the sociodemographic survey, which served as the basis for the subsequent stages of data collection. Of these 42 individuals, 32 participated in the qualitative interviews, and 20 took part in the community assembly. Participants emphasized snakebite envenoming as a significant health issue, though not the only one, and reported frequent encounters with snakes, underscoring its severity as a concern. The qualitative analysis identified three main themes: Snakebites in the Community, which focused on personal experiences with snakes; Common Health Problems, which addressed other health issues faced by community members; and Community Defining Solutions, which discussed strategies and solutions proposed by the community to address these challenges. Conclusions/significance Improvements in health care delivery to populations living in Amazonian communities are possible with the judicious use of tested integrated interventions, particularly when the community identifies various concurrent health problems. SBE control programs in remote areas of the Brazilian Amazon should be planned with a multidisciplinary and intercultural approach, preferably integrated with broader interventions that address the population's needs for a range of health issues.